Secretome Hypoxia-Mesenchymal Stem Cells Regulate IL-10 Concentrations in STZ-induced Type 1 Diabetes Rats - Sutrisman, Intan Permatasari; Antari, Arini Dewi; Putra, Agung; Irawan, Risky Chandra; Handoyo, Frigi Eko (International Journal of Cell and Biomedical Science, 2022)
Background: Type 1 Diabetic Mellitus (T1DM) is a well-known autoimmune disease that is characterized by a specific adaptative immunity against β-cell antigens. Mesenchymal stem cells (MSC) have emerged as potential immunomodulators in a paracrine manner via their bioactive soluble molecules that involve inflammation-related diseases, including T1DM. Objective: This study aims to investigate the effect of S-HMSC on regulating IL-10 concentrations in STZ-induced T1DM rats. Materials and Methods: This study uses a post-only control group design and randomized system. To induce T1DM rats, an intraperitoneal injection (65 mg/kg BW) of streptozotocin (STZ) was inducted. 20 Wistar rats were subdivided into the following groups: T1DM, DM with 0,5cc S-HMSC (Low-dose), and DM with 1cc S-HMSC (High-dose). The animals received an intraperitoneal injection of S-HMSC once a week for up to 4 weeks. On day 28, the animals were terminated and IL-10 concentrations were measured by ELISA. Results: After S-HMSC administration, the concentration of IL-10 in the treated group was increased in either low-dose or high-dose groups compared with the T1DM group. Conclusion: Administration of secretome-hypoxia MSC may regulate IL-10 concentrations in STZ-induced Type 1 Diabetes Rats.